Introduction - Seabra, P.; Carvalho, C.; Ribeiro, I. M. (Cadernos de Estudos Africanos, 2022)
Since the inception of the European Communities, Africa has been on the horizon for the development of foreign and diplomatic relations, largely due to European states’ will to maintain relations with former colonies and to exert some form of normative power (Haastrup, 2013). However, both the institutional developments in practice and the study of European-African relations have been marked by an asymmetrical hierarchical relationship imbued with post-colonial characteristics. Reasons for this state of affairs are often attributed to Africa being a complex continent with more than fifty countries with porous and volatile border areas and differentiated relationships with both the European Union (EU) and its Member States. On the other hand, Europe is also made up of a myriad of different states with very different and oftentimes complex historical relationships with African countries.